Implementasi Peraturan Daerah Kabupaten Badung Nomor 10 Tahun 2017 tentang Kawasan tanpa Rokok pada Tempat Wisata - Karinka; I Ketut Sukadana; I Nyoman Sutama (Fakultas Hukum, Universitas Warmadewa, 2020)
Smoking belongs to the right of all people, but smoking can interfere with Human Rights because the distribution of cigarette smoke produced by smokers can interfere with the health of people around. In Bali, tourist attractions are one of the non-smoking areas. This is stated in the Regional Regulation of Badung No. 10 of 2017 concerning Non-Smoking Areas. Related to this, the study examines two things, that is, the regulation of No-Smoking Areas in the tourist attractions in Badung Regency and the implementation of the Regional Regulation of Badung No. 10 of 2017 on the tourist attractions. The research method used is empirical legal research that is conducting a direct research followed by analyzing data and presented in qualitative manner. In its regulation, Civil Service Police Unit (Satpol PP) as the enforcer of the regional regulation has conducted supervision on tourist attractions and sanctions given in accordance with the Article 21 Number (10) of 2017 of the Badung Regency Regional Regulation. Its application has been done through socialization to the manager of tourist attractions, but the lack of public knowledge about the non-smoking areas in tourist attractions has been appearing as an inhibiting factor.